PENGARUH TIPE KEPEMIMPINAN DAN KARAKTERISTIK GURU TERHADAP KONFLIK KERJA GURU DI SD NEGERI PONTIANAK TIMUR - Yanto, Delvi; M. Amin, Maswardi; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ There are 22 elementary schools in East Pontianak spread across seven villages, namely: major ditch, Banjar Sarasan, Saigon, Tanjung Hulu, Tanjung Hilir, in Bugis and Tambelan Sampit. In implementing education, it does not rule out the possibility of conflict. This study aimed to analyze the effect of leadership type and teacher characteristics towards teacher work conflict in East Pontianak State Elementary School. This study used a quantitative approach that is descriptive correlational. The population used was all teachers in the East Pontianak Public Elementary School with sample totaling 80 people. This study showed that the effect of leadership type and teacher characteristics together to teacher work conflict was 58.5%, while F count> F table (20.842> 2.21) and p <0.05 (p = 0.000 < 0.05) it can be stated that the variance of teacher work conflict variables can be significantly influenced by the type of leadership and teacher characteristics and separately the influencing variables namely leadership type and gender. It can be concluded study that leadership types significantly influence teacher work conflict. Â Key Words: Leadership Type, Teacher Characteristics, Teacher Work Conflict Â